Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


The standard form of the equation is either -2 x^{2} +6x-1=0, with a=-2, b=6, and c=-1, or 2 x^{2} -6x+1=0, with a=2, b=-6 and c=1.
0 0 0
To write the quadratic equation in standard form youll have to identify a,b,c whereas a=-2x^2 b=6x c=-1 youll have to transpose this using the quadratic equation ax^2+bx+c=0. thus completing your quadratic equation in standard form. the answer= -2x^2+6x-1=0
0 0 0
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts